Two new species of Herina (Diptera: Ulidiidae) from the Mediterranean region, with key to species groups - Morgulis, E.; Freidberg, A.; Kameneva, E. P. (Zootaxa, 2013)
Herina dimorphica n. sp. (type locality Israel) and H. sicula n. sp. (type locality Sicily, Italy) are described and illustrated, and a new species group (the Herina dimorphica species group) is established for both species. H. dimorphica is characterized by a sexually-dimorphic wing pattern and venation. H. sicula is similar albeit not sexually-dimorphic. Almost all known Herina species are assigned to one of nine species groups, which are keyed.